Football training module for small sided game under national football development plan - Mohamad, Shamsul Kamar; Karim, Zulakbal Abd; Akbar, Amin (Jurnal Patriot, 2025)
Problems: A national football philosophy or DNA was introduced to shape coaches to become players who not only have technical and tactical expertise, but also have their own style of play. Purpose: This study was conducted to identify the syllabus used to coach the District Training Centre (PLD) football team in Kuala Lumpur. The coaching process can be improved by having a source of knowledge and knowing what the syllabus of the sport is. Coaches need to build a wide knowledge space to adapt to environmental conditions. Methods: This qualitative study aims to identify what is the training syllabus used by the football coaches of District Training Centre of Kuala Lumpur. A total of seven trainers from the District Training Centre in Kuala Lumpur, who are also teachers, were involved as participants in the study and were interviewed to obtain data. The data from the interviews were analyzed using the 'thematic analysis' method. The number of participants for the study were determined by the level of "saturation of information", where the participants were interviewed until they were found to be unable to present new data compared to the previous participants. Results: Based on the research conducted, there are three approaches used, namely (i) tactical, (ii) knowledge of managing players and (iii) systematic training. By using the three approaches, coaches can diversify their teaching methods when coaching their football team, which can be used to build a good training program. Conclusion: these three syllabi or method can be used to build a good football training programme and help coaches to coach their District Training Centre (PLD) football teams.